Pengaruh Pertumbuhan Ekonomi, Suku Bunga, Inflasi, dan Perpajakan terhadap Investasi di Indonesia: Analisis Periode 2003-2022 - Ariyadi, Ridho; Yunani, Ahmad; Sopiana, Yunita (Ecoplan, 2024)
The purpose of this study is to examine how taxes, interest rates, inflation, and economic growth affect investment in Indonesia. The variables analyzed included economic growth, interest rates, inflation, and taxes in relation to investment in Indonesia. The study used time series data from 2003 to 2022 and applied quantitative analysis, focusing on measurable data presented through equations, tables, and other formats. The empirical findings indicate that interest rates and economic growth both have a positive and significant impact on investment. While taxes also show a positive impact, their effect is not statistically significant. In contrast, inflation has a negative impact on investment. These findings may provide valuable insights for policymakers in formulating strategies to promote investment in Indonesia.